1984
DOI: 10.1007/bf00253278
|View full text |Cite
|
Sign up to set email alerts
|

Role of elective brain irradiation during combined chemoradiotherapy for limited disease non-small cell lung cancer

Abstract: We have studied the clinical impact of elective brain irradiation (EBI) in patients with locally advanced, non-small cell lung cancer (LA-NSC). All patients received combination chemotherapy (cyclophosphamide + doxorubicin (Adriamycin) + cisplatin = CAP) or CAP plus radiotherapy as the initial treatment for their active tumor or as an adjuvant therapy. Of 97 evaluable patients, 46 were randomized to receive EBI (3 000 rad in 10 fractions given over two weeks). The characteristics of both groups were comparable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
123
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(126 citation statements)
references
References 27 publications
3
123
0
Order By: Relevance
“…55 The incidence of brain metastases was markedly decreased with PCI (4% vs 27%; P < .01), although there was no difference in survival secondary to extracranial progression. In this study, PCI significantly reduced the incidence of brain metastases only in those with squamous-cell histology.…”
Section: Biological Predictorsmentioning
confidence: 86%
“…55 The incidence of brain metastases was markedly decreased with PCI (4% vs 27%; P < .01), although there was no difference in survival secondary to extracranial progression. In this study, PCI significantly reduced the incidence of brain metastases only in those with squamous-cell histology.…”
Section: Biological Predictorsmentioning
confidence: 86%
“…Although randomized studies have failed to establish a survival benefit for PCI, subset analysis was not performed and it remains possible that selected patients, particularly those without evidence of disease at the primary or other extracranial sites, may significantly benefit from the prevention of brain metastasis. [10][11][12][13] Likewise, some studies have suggested that early detection of brain metastasis from NSCLC and prompt treatment with SRS can significantly improve survival, particularly among those without evidence of extracranial disease. 14,15 Whereas the optimal local-regional treatment approach for locally advanced NSCLC is uncertain, the integration of surgery as a component of multimodality therapy may enable the identification of a subset of patients, those with a pathological complete response (pCR) to neoadjuvant chemotherapy or chemoradiotherapy, who may be at high risk for the subsequent development of brain metastases.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] However, these results have been criticized because of patient heterogeneity and for possible imbalances in stratification according to established prognostic variables. It is unknown to what extent the development of local-regional failure or extracranial disease progression may have obscured any potential benefits that PCI may have conferred.…”
Section: Discussionmentioning
confidence: 99%
“…[18] Six randomised controlled trials have evaluated the role of PCI in LA-NSCLC, with five studies demonstrating a statistically significant reduction in the incidence of BM with PCI, but no survival advantage. [10,[19][20][21][22][23] The most recent of these studies was underpowered for a survival endpoint. [10] It is not clear whether patient refusal was the reason why target accrual was not met.…”
Section: Discussionmentioning
confidence: 99%